PENGARUH PEMEDIASIAN KOMITMEN ORGANISASIONAL DALAM HUBUNGAN ANTARA KEPUASAN KERJA DAN INTENT TO LEAVE Studi pada Rumah Sakit di Yogyakarta - Yuni Siswanti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2006)
The purpose of this research is to examine the influence of organizational commitment as mediatingvariable in relation between job satisfaction and intentto leave. The samples were nurses those workingat DKT, Panti Rapih, Bethesda, and PKU Muhammadiyah hospital’s in Jogjakarta. Of the 126 questionnaires were distributed to the nurses, 107 data that can employ on this study.The data were collected use 4-item job satisfaction, 6-item for each three dimension organizational commitment, 3-itemintnt to leave. The overall instruments those used in this study were perceptive instruments.Simple regression analysis was used to examinethe influence independent variable todependent variable.Regression analysis (Ballon and Kenny Model’s) wasused to examine whether organizational commitmentbecome mediating variable in relationbetween job satisfaction and intent to leave.